2018
DOI: 10.1675/063.041.0102
|View full text |Cite
|
Sign up to set email alerts
|

Space Use and Movements of Adult Reddish Egrets (Egretta rufescens) During Winter

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…For example, most of the samples from Louisiana were collected from a small colony on an island, which did not have documented nesting Reddish Egrets until recently (Selman & Davis, 2015). Therefore, the unique genetic deme in Louisiana, which also included some individuals from Florida (Figure 1d) (Geary et al, 2015;Koczur et al, 2018;Lamb et al, 2017), we found little evidence to support that immigrants breed at high frequencies with TA B L E 3 Analysis of Molecular Variation (AMOVA) tests for four different management unit (MU) models ( Figure 1a) Regarding dispersal, Geary et al (2015) found only one female out of four dispersed greater than 120 km from their natal colony, whereas 13 out of 21 males dispersed greater than 120 km.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, most of the samples from Louisiana were collected from a small colony on an island, which did not have documented nesting Reddish Egrets until recently (Selman & Davis, 2015). Therefore, the unique genetic deme in Louisiana, which also included some individuals from Florida (Figure 1d) (Geary et al, 2015;Koczur et al, 2018;Lamb et al, 2017), we found little evidence to support that immigrants breed at high frequencies with TA B L E 3 Analysis of Molecular Variation (AMOVA) tests for four different management unit (MU) models ( Figure 1a) Regarding dispersal, Geary et al (2015) found only one female out of four dispersed greater than 120 km from their natal colony, whereas 13 out of 21 males dispersed greater than 120 km.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by well-defined demes for Baja California, Chiapas, and the Bahamas (Figure 1d Florida has two haplotypes in total. One of them is Haplotype 3, which is expected given the short-distance movements by female's between Florida and the Bahamas inferred from banding and telemetry data (Geary et al, 2015;Koczur et al, 2018;Lamb et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Advanced tracking methods (e.g., ARGOS or GPS tracking) gather real-time data with accurate location information that traditional bird surveys cannot provide. The resolution of these data can account for variation in movement and habitat use ( Koczur et al, 2018 ; Takano & Haig, 2004 ), thereby enhancing our ability to evaluate the habitat quality for birds and yield data to guide habitat management and conservation (e.g., El-Hacen et al, 2013 ; Mitchell et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%